2017
DOI: 10.2527/jas2017.1733
|View full text |Cite
|
Sign up to set email alerts
|

TRIENNIAL LACTATION SYMPOSIUM/BOLFA: Mammary growth during pregnancy and lactation and its relationship with milk yield1

Abstract: The number of secretory cells in the mammary gland is often cited as a major determinant of milk production. However, literature data for proxy measures of secretory cell number do not fully support such a claim. In particular, measurements of total mammary DNA in livestock explain only <25% of variation in milk yield, probably because of tissue heterogeneity for DNA concentration. Relative to BW, measurements of udder size in dairy cattle, as total DNA or udder weight, are approximately double those seen in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 87 publications
(120 reference statements)
3
17
0
1
Order By: Relevance
“…Most mammary growth takes place through pregnancy. Mammary gland cell proliferation and differentiation have a great impact on milk yield and lactation persistency [53]. As expected, must identified genes and GO terms have a role in milk production or mammary gland development which means feeding lambs by milk have the most impact on weight gain rather than other maternal effects.…”
Section: Gwas and Gsa Of Maternal Composite Traits At Weaningsupporting
confidence: 57%
“…Most mammary growth takes place through pregnancy. Mammary gland cell proliferation and differentiation have a great impact on milk yield and lactation persistency [53]. As expected, must identified genes and GO terms have a role in milk production or mammary gland development which means feeding lambs by milk have the most impact on weight gain rather than other maternal effects.…”
Section: Gwas and Gsa Of Maternal Composite Traits At Weaningsupporting
confidence: 57%
“…However, Jenkins et al (2016) reported that cows with either short or long GL produced less milk, fat, and protein than those with an average GL. The association between GL and lactation performance can be partly explained by this fact that the greatest increase in the mass of parenchymal tissue occurs in late pregnancy (Davis, 2017); therefore, shorter the GL, less the mammary cells, and subsequently less the milk yield. In addition, it may be concluded that multiparous cows with a longer GL would have a longer dry period and more time for udder tissue recovery which can result in a higher partial and 305-d lactation performance (Norman et al, 2011;Atashi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…During lactation, no further mammogenesis that might modulate milk production occurs in bovine species (Akers, 2017a,b;Davis, 2017). Although rearing in early life significantly affects growth and later performance (Kaufhold et al, 2000), adult cows may adapt differentially to successive lactations, with a clear effect of the dry period between (Gabai, 2003;Chen et al, 2016a,b).…”
Section: Consequences Of Feeding Intensity and Management For Mammarymentioning
confidence: 99%